(untitled) (Хабаршы. Психология және социология сериясы, 2022)
Environmental problems in Kazakhstan are serious issues to be dealt with, as it ranges from problems of water shortages to nationwide land degradation issues. Within that, one particular problem sticks out that has yet not been significantly scholarly studied. The problem of environmental awareness issue has been known to play a crucial role in sustainable development and pro-ecological programs and policies, as for more than five decades’ various Western researcher works have outlined the positive effects of raising the level of environmental awareness among different groups of population. However, this spe- cific research area has not been thoroughly studied in the context of a Central Asian region, particularly that of Kazakhstan. In light of these problems, this research paper aims to provide a critical literature review on environ- mental awareness studies in the context of Kazakhstan by examining prominent local and international scholarly works on this subject matter. Hence, the objectives of this paper is to provide a foundation of knowledge on the topic; identify research gaps to prevent research inconsistencies; uncover previous research findings and research methodologies used; and compare and contrast the research findings in order to answer unresolved open questions. For that, a total of 82 studies were analyzed. Key words: Kazakhstan, environmental awareness, literature review, content analysis.